(untitled) (SCI-TECH LENS, 2026)
Fast charging technology improves user convenience by significantly reducing charging time, but it also accelerates battery degradation through increased electrochemical and thermal stress. Battery Management Systems (BMS) mitigate these effects using advanced charging protocols, thermal management techniques, and intelligent control strategies. Despite recent advancements in power electronics and AI-driven optimization, the trade-off between charging speed and battery longevity remains a major challenge, particularly in tropical regions such as the Philippines where high ambient temperatures further affect battery performance and safety.